2018
DOI: 10.1007/s40266-018-0551-5
|View full text |Cite
|
Sign up to set email alerts
|

Time in Therapeutic Range of Oral Vitamin K Antagonists in Hospitalized Elderly Patients

Abstract: Both our results and those in the literature indicate that TTR in geriatric populations is lower than that in the general population. Most patients had an insufficient TTR, exposing them to an increased risk of thromboembolic and hemorrhagic events. These data provide a perspective on poor-quality anticoagulation and illustrates the difficulty of using VKAs in geriatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Additionally, we found that vitamin K is positively and significantly associated with TSH, TC, LDL, and sdLDL levels. Oral vitamin K antagonists (VKAs) have been shown to alter TSH levels in elderly hospitalized patients, 29 a variable directly linked to the development of depression. 30 Moreover, vitamin K might positively impact serum lipids and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that vitamin K is positively and significantly associated with TSH, TC, LDL, and sdLDL levels. Oral vitamin K antagonists (VKAs) have been shown to alter TSH levels in elderly hospitalized patients, 29 a variable directly linked to the development of depression. 30 Moreover, vitamin K might positively impact serum lipids and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The safety profile is as good as in younger patients, with the only increased risk being for nonfatal gastrointestinal bleeding [23]. It is important to note that, in geriatric populations, the time in the therapeutic range (TTR) of VKAs tends to be lower than in the general population: this means that most patients are exposed to an increased risk of thromboembolic and hemorrhagic events [24]. Additionally, VKA prescription can be motivated by the concern for the renal dysfunction typically present in elderly patients: in fact, even in our population, CKD was one of the most frequent comorbidities, and the hepatic metabolism of VKAs could lead the physicians to prefer drugs potentially less deleterious for these patients.…”
Section: Discussionmentioning
confidence: 99%